Systematic investigation and modeling of piezoelectric interaction with loading structures - Tjahjowidodo, Tegoeh (2020)
Piezoelectric actuators are spreading their applications in a variety of engineering systems, e.g., a compression mechanism with large force and high-precision motion systems. A systematic investigation of the dynamics of piezoelectric actuators that interact with loading structures is becoming requisite. This article discusses the dynamic model by merging constitutive equations of the piezoelectric material and the dynamics of loading structures. The dynamic behavior of piezoelectric actuators that interacts with loading structures depends on the stiffnesses of both entities. Two of the most common operating conditions of the actuator, based on its interaction with the loading structures, are classified and considered in this study: fixed–free and free–free conditions. The proposed dynamic models are subsequently validated on real mechanisms with satisfactory results. It is shown that the models are capable of capturing the dynamic interaction between the actuators and loading structures.